Geographic Heterogeneity in Otolaryngology Medicare New Patient Visits - Hur, Kevin; Gibbons, Joseph; Finch, Brian Karl (Otolaryngology-head and neck surgery, 2020)
To analyze the spatial variation of sociodemographic factors associated with the geographic distribution of new patient visits to otolaryngologists. Retrospective cross-sectional analysis. United States. Medicare new patient visits pooled from 2012 to 2016 to otolaryngology providers were obtained from the Centers for Medicare and Medicaid Services, and county-level sociodemographic data were obtained from the 2012-2016 American Community Survey. The mean number of new patient visits per otolaryngology provider by county was calculated. The spatial variation was analyzed with negative binomial and geographically weighted regression. Predictors included various neighborhood characteristics. There were 7,199,129 Medicare new patient visits to otolaryngology providers from 2012 to 2016. A 41.7-fold difference in new patient evaluation rates was observed across US counties (range, 11-458.8 per otolaryngology provider). On multivariable regression analysis, median age, sex, work commute time, percentage insured, and the advantage index of a county were predictors for the rate of new patient visits to otolaryngology providers. However, geographically weighted regression demonstrated that the association of a county's disadvantage index, advantage index, percentage insured, and work commute times with new patient visits per provider varied across space. There are wide geographic differences in the number of new Medicare patients seen by otolaryngologists, and the influence of county sociodemographic factors varied regionally. Further research to analyze the variations in practice patterns of otolaryngologists is warranted to predict future public health needs.